Riboflavin Depletion Promotes Tumorigenesis in HEK293T and NIH3T3 Cells by Sustaining Cell Proliferation and Regulating Cell Cycle–Related Gene Transcription. Issue 6 (7th May 2018) - Long, Lin; He, Jian-Zhong; Chen, Ye; Xu, Xiu-E; Liao, Lian-Di; Xie, Yang-Min; Li, En-Min; Xu, Li-Yan
Abstract: Background: Riboflavin is an essential component of the human diet and its derivative cofactors play an established role in oxidative metabolism. Riboflavin deficiency has been linked with various human diseases. Objective: The objective of this study was to identify whether riboflavin depletion promotes tumorigenesis. Methods: HEK293T and NIH3T3 cells were cultured in riboflavin-deficient or riboflavin-sufficient medium and passaged every 48 h. Cells were collected every 5 generations and plate colony formation assays were performed to observe cell proliferation. Subcutaneous tumorigenicity assays in NU/NU mice were used to observe tumorigenicity of riboflavin-depleted HEK293T cells. Mechanistically, gene expression profiling and gene ontology analysis were used to identify abnormally expressed genes induced by riboflavin depletion. Western blot analyses, cell cycle analyses, and chromatin immunoprecipitation were used to validate the expression of cell cycle–related genes. Results: Plate colony formation of NIH3T3 and HEK293T cell lines was enhanced >2-fold when cultured in riboflavin-deficient medium for 10–20 generations. Moreover, we observed enhanced subcutaneous tumorigenicity in NU/NU mice following injection of riboflavin-depleted compared with normal HEK293T cells (55.6% compared with 0.0% tumor formation, respectively). Gene expression profiling and gene ontology analysis revealed that riboflavin depletion induced the expression of cell cycle–related genes. Validation experiments also found that riboflavin depletion decreased p21 and p27 protein levels by ∼20%, and increased cell cycle–related and expression-elevated protein in tumor (CREPT) protein expression >2-fold, resulting in cyclin D1 and CDK4 levels being increased ∼1.5-fold, and cell cycle acceleration. We also observed that riboflavin depletion decreased intracellular riboflavin levels by 20% and upregulated expression of riboflavin transporter genes, particularly SLC52A3, and that the changes in CREPT and SLC52A3 correlated with specific epigenetic changes in their promoters in riboflavin-depleted HEK293T cells. Conclusion: Riboflavin depletion contributes to HEK293T and NIH3T3 cell tumorigenesis and may be a risk factor for tumor development.